(untitled) (Conferencea, 2024)
Investment projects serve as the foundation of economic development, technological development and social welfare. They involve the allocation of financial resources to a particular enterprise with the expectation of obtaining positive returns and achieving strategic goals. Investment projects can be divided into several categories based on various criteria, such as the nature, scale and sector of investment. Some common types include: Public investment projects are important for the growth and development of economies around the world. They are usually financed by governments or public sector entities in order to improve public infrastructure, provide public services or stimulate economic development. These projects cover a wide range of sectors, including transport, health, education and utilities. According to the World Bank, public investment projects have been an important tool for governments around the world, especially in developing economies. For example, in 2021, public investment in infrastructure for developing countries averaged about 4% of GDP. This figure shows that governments are investing heavily in public investment projects to stimulate economic growth and improve the quality of life.